Konsep Jilbab dalam Perspektif Al-Qur’an dan Relevansinya dengan Tujuan Pendidikan Islam - Susanti Susanti; Eni Fariyatul Fahyuni (Universitas Muhammadiyah Jember, 2021)
Thie inspiration for this study came from the emergence of modern hijab models and designs, most of which are still far from the criteria for the syar’i hijab. So that the hijab is currently only used as part of a lifestyle which Islamic law, as written in the al-Qur’an and As-Sunnah. Besides, because of the lack of public knowledge about the obligatory veil. This type of research is library research. The data in this article are presented in the form of qualitative data. So that it is presented in non-numeric from namely in the form of sentences, statements and description. In this case the writer examined the material from various literary sources related in relation to the statement of the veil in the perspective of the al-Qur’an and its relation to Islamic education. Then the writer performed data analysis and drew a conclusion. This study's finding are presented that the criteria for the syar’i headscraf are as follows: hijab must be able to cover all parts of woman body, and the cloth used must be thick and loose enough not to expose the curves of the body, besides that the clothes be similar to the clothes of the opposite sex, and when wearing them it must not be intended to be decorated, not to gain popularity. In addition, this study also that there is a very relevant relationship between to the concept of the veil in the al-Qur’an and the objectives of Islamic education.